2012
DOI: 10.1016/j.bmc.2012.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Development of novel antibacterial agents against methicillin-resistant Staphylococcus aureus

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) poses a serious threat to public health because of its resistance to multiple antibiotics most commonly used to treat infection. In this study, we report the unique ability of the cyclooxygenase-2 (COX-2) inhibitor celecoxib to kill Staphylococcus aureus and MRSA with modest potency. We hypothesize that the anti-Staphylococcus activity of celecoxib could be pharmacologically exploited to develop novel anti-MRSA agents with a distinct mechanism. Examination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…Another study by Chiu et al (2009) found that celecoxib inhibited the growth of Francisella tularensis and F. novicida . In addition, celecoxib also exhibited antibacterial activity against S. aureus and S. epidermidis ( Chiu et al, 2012 ). Apart from antimicrobial activity, celecoxib inhibits multidrug efflux pumps in Mycobacterium smegmatis and S. aureus , and increases the sensitivity of bacteria to various antibiotics, including ampicillin, kanamycin, ciprofloxacin, and chloramphenicol ( Kalle and Rizvi, 2011 ; Annamanedi and Kalle, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another study by Chiu et al (2009) found that celecoxib inhibited the growth of Francisella tularensis and F. novicida . In addition, celecoxib also exhibited antibacterial activity against S. aureus and S. epidermidis ( Chiu et al, 2012 ). Apart from antimicrobial activity, celecoxib inhibits multidrug efflux pumps in Mycobacterium smegmatis and S. aureus , and increases the sensitivity of bacteria to various antibiotics, including ampicillin, kanamycin, ciprofloxacin, and chloramphenicol ( Kalle and Rizvi, 2011 ; Annamanedi and Kalle, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among them are SID 3 (dasatinib monohydrate), a new kind of multitargeted inhibitor of several critical oncogenic kinases for the treatment of thyroid cancer (Roy et al, 2012); SID4 (carboplatin), a kind of antineoplastic agent used mainly for the treatment of human cancer via interfering with DNA synthesis (Banerji et al, 2008); SID14 (ulixertinib, BVD-523), a highly potent, selective, and reversible ERK1/2 inhibitor used for the treatment of advanced solid tumors (Mendzelevski et al, 2018); SID 15 (pimobendan), a phosphodiesterase III inhibitor used for the treatment of chronic and acute heart failure (Iwasaki et al, 1999); and SID 20 (tolfenamic acid), a traditional antiinflammatory compound that acts as a kind of cyclooxygenase inhibitor commonly used for the treatment of inflammationrelated diseases (Feldman et al, 2018). However, researchers recently found new applications for cyclooxygenase inhibitors, such as celecoxib, that possess bactericidal effects against some pathogenic bacteria (such as Staphylococcus aureus, Bacillus anthracis, and Pseudomonas aeruginosa) (Chiu et al, 2012;Thangamani et al, 2015). The new application of conventionally approved drugs has recently received increasing attention.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical options that currently exist to treat MRSA are summarized in Introduction [173]. MRSA treatment guideline was prepared by an Expert Panel of the Infectious Diseases Society of America (IDSA) [174].…”
Section: Discussionmentioning
confidence: 99%